THE EXERCISE OF PUBLIC HEALTH POWERS IN MENTAL HEALTHCARE - THE IMPACT ON PUBLIC SAFETY - Losevich, Marina; Konstantinova, Karīna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
To ensure public safety, most European states have statutory powers enabling a range of compulsory interventions for persons with infectious diseases and mental disorders. The evidence of their meaningfulness in mental health patients is dubious, especially regarding their preventive effect on public safety. To reveal the mental health services' impact on violent offense commissions after discharge from involuntary inpatient care, a retrospective three-case series study was conducted. A scoping literature review was performed to construct the recommendations for practice improvement and further studies. Based on individual clinical expertise, the common issues in delivering involuntary mental healthcare in Latvia are described. To conclude, coercive psychiatric interventions shall be considered as a part of internal security and human rights protection and, therefore, shall be surveilled, in line with communicable diseases. Legal mechanisms (temporary protection against violence, coercive measures of a medical nature) are not effective against persons with severe mental illness and fail to prevent violent incidents. By the time being, during involuntary admission and treatment, the patient is subjected to various safety risks, that are inconsistent with the basic rights or best interests, and thus determines the state's obligation to promote voluntary treatment and provide the least restrictive approach.